ANTIOXIDANT PROTECTION OF ACTIVE PRODUCTS FROM GRAPES - Gulmira Irgasheva; Khakimova S. Sh. (Journals Park Publishing, 2022)
Enzymes entering into the system of oxidising protection of a work cycle of processing of white and red grades of grapes are studied. It is established that some technological operations predetermine strengthening of oxidizing stress. At processing of red grapes connected forms SO2 that reduces it's antioxidant properties increase. Sulfation a red mash in the quantity provided by the technological instruction obviously not enough for maintenance of antioxidant of protection.
Keywords: Enzymes, antioxidant protection, catalase, superoxide dismutase, peroxidase, oxidation, dismutation, sulfitation, oxygen.